PROCESSING METHOD AND DROSS DUST FRACTIONS PROPERTIES IN THE CONFAL Inc. - Sedo, Jan (European Scientific Journal, ESJ, 2015)
Dross processing and its dust non-melting fractions is an important area for the producers of this type of waste and also for the products consumers. It is possible to produce the products from the waste. The Confal Inc. company creates its own production process, which is more economically advantageous in comparison with the previous used method. To handle this process, it offers promising future prospects for small companies which are so far from the major processors of dust dross. To contribute to the protection of the environment in any form, it is the responsibility of each producer and consumer.